Society Against the State in Marc Richir - Névot, Aurélie (Laval théologique et philosophique, 2025)
The Amerindian ethnology developed by Pierre Clastres played an important role in the political phenomenology of Marc Richir. By first referring to this anthropologist, who is part of the “anarchist” movement, and then more extensively discussing the Richirian phenomenology that draws on him, it appears that while, for Richir, the symbolic fixes the phenomenological and disarms its anarchic charge, with the State acting as a barrier to the anarchy of revolutionary phenomena, a form of inverted system would be observable in the “societies against the State” described by Clastres. Insofar as these so-called “primitives” would perceive the State as a generator of chaos, they would institute a society with chiefs who would have no coercive power to overrule it, thereby setting the State aside from their own political system. This contribution aims to explain Richir’s reading of Society Against the State.